Animals and society an introduction to human-animal studies - DeMello, Margo 1964- (Columbia University Press, 2021)
"Human-animal studies is an interdisciplinary field that explores the spaces that animals occupy in human social and cultural worlds. It examines the interactions humans and animals have with each other and the ways animal lives intersect with human societies. Since existing social orders rely on the exploitation of animals to serve human needs, the questions posed by human-animal studies touch upon a wide range of fundamental issues. Animals and Society provides a broad overview of this rapidly growing field. Margo DeMello offers students and scholars a holistic and comprehensive picture of the state of inquiry into the relationships that exist between humans and other animals. She considers interactions between animals and humans in social organizations, such as the family, the legal system, and political and religious institutions. A major focus is the social construction of animals in world cultures and the way in which these social meanings are used to reinforce and perpetuate hierarchical human relationships such as racism, sexism, and class privilege. The book also examines how different human groups construct a range of identities for themselves and for others through animals. This second edition of Animals and Society is fully updated and expanded throughout, enhancing the book's relevance for student and activist readers alike. It includes many new international examples, all-new case studies, and updated supplementary readings"--
Keywords: Mensch; Beziehung; Tiere; Human-animal relationships; Human-animal relationships / History; Animals and civilization / History